2019
DOI: 10.1038/s41598-019-48043-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of AGP Fucosylation as a Marker for Hepatocellular Carcinoma of Three Different Etiologies

Abstract: A mass spectrometric analysis platform has been developed to determine whether glycosylation patterns of alpha-1 acid glycoprotein (AGP) could be used as a marker for early detection of hepatocellular carcinoma (HCC) in different etiologies, i.e. non-alcoholic steatohepatitis (NASH), alcoholic liver disease (ALC), and hepatitis C virus (HCV). MALDI-MS profiling of N -glycans of AGP purified from 20 μL of patient serum in HCC (n = 72) and liver cirrhosis (n = 58) showed that a unique trif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Alpha-1 acid glycoprotein (AGP) is an acute-phase glycoprotein synthesized mainly by hepatocytes and has different glycoforms dependent on the pathophysiological conditions (152), and multifucosylated AGP can be used as a novel biomarker for HCC (153). Liang et al (154) found the trifucosylated N-glycan of AGP presented in HCC patients but absent in healthy controls and most cirrhosis patients and could differentiate HCC from cirrhosis with AUROCs of 0.707-0.751 in various causes of liver diseases and exhibited an AUROC of 0.709, sensitivity of 52%, and specificity of 80% for differentiating ANHC from LC. These results suggest that the AGP could serve as a potential marker for diagnosing HCC, including ANHC.…”
Section: Agpmentioning
confidence: 99%
“…Alpha-1 acid glycoprotein (AGP) is an acute-phase glycoprotein synthesized mainly by hepatocytes and has different glycoforms dependent on the pathophysiological conditions (152), and multifucosylated AGP can be used as a novel biomarker for HCC (153). Liang et al (154) found the trifucosylated N-glycan of AGP presented in HCC patients but absent in healthy controls and most cirrhosis patients and could differentiate HCC from cirrhosis with AUROCs of 0.707-0.751 in various causes of liver diseases and exhibited an AUROC of 0.709, sensitivity of 52%, and specificity of 80% for differentiating ANHC from LC. These results suggest that the AGP could serve as a potential marker for diagnosing HCC, including ANHC.…”
Section: Agpmentioning
confidence: 99%
“…In related work, Liang et al applied MALDI‐MS glycan profiling to AGP from serum where AGP was isolated with a chemical precipitation method. The AGP glycan profile was more complex than Hp, and yielded nine peaks in the MALDI MS spectrum.…”
Section: Discovery—mass Spectrometry‐based Assaysmentioning
confidence: 99%
“…AGP glycosylation pattern is rather complex and heterogeneous [reviewed in detail by Fournier et al (2000) ; and further studied by Fernandes et al, 2015 ]. Multiple glycan combinations have been detected in the plasma of healthy humans ( Treuheit et al, 1992 ; Ongay and Neususs, 2010 ; Baerenfaenger and Meyer, 2018 ; Keser et al, 2021 ) and changes under pathological states have been reported ( De Graaf et al, 1993 ; Liang et al, 2019 ; Keser et al, 2021 ). More specifically, branches with sialic acid are also fucosilated creating highly biologically active sialyl-Lewis X epitopes (sLe x ).…”
Section: Agp Definition and Molecular Characteristicsmentioning
confidence: 99%